Ndebele Girls as Knowers: Menstrual Preparation and Sanitary Preferences in Zimbabwe. Issue 1 (1st March 2023) - Ncube, Nolwazi Nadia
Abstract: In this article, I examine critically the framing of the African girl child in international development discourse on menstruation and menstrual activism and address the question, "What influence have African girls had on policy or programs and to what extent have they been mere targets and objects of such policies and programs?" I analyze baseline interviews I carried out at the inception of a Zimbabwean sanitary wear intervention and shine a light on African girls as potential guides and consultants in constructing policy and programs. I show how the communitarian, Ubuntu -centred family values of rural Ndebele people provide a counterpoint to colonial and neoliberal Western-centred development approaches in addressing challenges girls face in relation to menstrual preparation and early unintended pregnancy.